The new encyclopedia britannica in 30 volume, macropedia VOL. 3 / William Benton - Benton, William (1977)
The landscape, people and population, the national economy, administration and social conditions, evolutionary origin and significance, physiology and biochemistry of bone, principal types of diseases and injuries, therapeutic and corrective measures.